Cryogenic MOS-Unit for LUCIFER - Hofmann, R; Mandel, H; Seifert, W; Seltmann, A; Thatte, N; Tomono, D; Weisz, H (2003)
We present a system for the exchange and handling of cold field masks in LUCIFER, the near infrared camera and spectrograph for the LBT. Inside the LUCIFER cryostat, 10 field-stop and long-slit masks, and 23 multi-slit masks are stored in a stationary and an exchangeable cabinet respectively. With LUCIFER at operating temperature, the exchangeable cabinet with its multi-slit masks can be transferred from the LUCIFER cryostat to an auxiliary cryostat, and a second cabinet harboring the newly made, pre-cooled masks can be transferred back to LUCIFER from. a second auxiliary cryostat. Inside LUCIFER, a robot transports the individual masks from their storage position in the cabinet to the focal plane, and inserts them in a mask mount where they are centered on two pins. The position accuracy of the masks in the focal plane is anticipated to be better than +/-10 mum. A mechanism which locks the masks in their cabinets and releases only the one connected to the transport robot permits mask exchange in arbitrary orientation of the cryostat.